Banking and Industrialization. Issue 6 (27th September 2018) - Heblich, Stephan; Trew, Alex
Abstract: We establish a causal role for banking access in the spread of the Industrial Revolution over the period 1817–1881 by exploiting unique employment data from 10, 528 parishes across England and Wales and a novel instrument. We estimate that a one standard deviation increase in 1817 finance employment increases annualized industrial employment growth by 0.93 percentage points. We establish the role of structural transformation as an underlying growth mechanism and show that banking access: (i) increases the industrial employment share; (ii) stimulates urbanization; and (iii) fosters inter-industry transition to high TFP, intermediate and capital-intensive sub-sectors.